Fatigability, Exercise Intolerance, and Abnormal Skeletal Muscle Energetics in Heart Failure - Weiss, Kilian; Schär, Michael; Panjrath, Gurusher S.; Zhang, Yi; Sharma, Kavita; Bottomley, Paul A.; Golozar, Asieh; Steinberg, Angela; Gerstenblith, Gary; Russell, Stuart D.; Weiss, Robert G. (Circulation. Heart failure, 2017)
Among central and peripheral factors contributing to exercise intolerance (EI) in heart failure (HF), the extent to which skeletal muscle (SM) energy metabolic abnormalities occur and contribute to EI and increased fatigability in HF patients with reduced or preserved ejection fraction (HFrEF and HFpEF, respectively) are not known. An energetic plantar flexion exercise fatigability test and magnetic resonance spectroscopy were used to probe the mechanistic in vivo relationships among SM high-energy phosphate concentrations, mitochondrial function, and EI in HFrEF and HFpEF patients and in healthy controls. Resting SM high-energy phosphate concentrations and ATP flux rates were normal in HFrEF and HFpEF patients. Fatigue occurred at similar SM energetic levels in all subjects, consistent with a common SM energetic limit. Importantly, HFrEF New York Heart Association class II-III patients with EI and high fatigability exhibited significantly faster rates of exercise-induced high-energy phosphate decline than did HFrEF patients with low fatigability (New York Heart Association class I), despite similar left ventricular ejection fractions. HFpEF patients exhibited severe EI, the most rapid rates of high-energy phosphate depletion during exercise, and impaired maximal oxidative capacity. Symptomatic fatigue during plantar flexion exercise occurs at a common energetic limit in all subjects. HFrEF and HFpEF patients with EI and increased fatigability manifest early, rapid exercise-induced declines in SM high-energy phosphates and reduced oxidative capacity compared with healthy and low-fatigability HF patients, suggesting that SM metabolism is a potentially important target for future HF treatment strategies.